The role of gender in participation and health among Slovenian youth - Kirbiš, Andrej (Studia Historica Slovenica, 2019)
The main purpose of our study was 1) to test for gender differences in subjective health and well-being, political and cultural participation; 2) to examine whether gender moderates the link between health and participation; and 3) to test for regional variation in this link. A representative survey sample of Slovenian Youth 2010 study was analysed. At the total sample levels, men reported better health, there were no gender differences in voter turnout, while cultural participation was higher among women. In addition, gender did not moderate cultural participation-health link (no significant link in either gender), but it did moderate voter turnout-health link, with turnout being significantly negatively related to health among men (but not among women). Regional variations were not detected, as associations within regions were largely insignificant.
Keywords: cultural participation; democracy; demokracija; enakost spolov; gender inequalities; health inequalities; kulturne razlike; mladi; political participation; regional differences; Slovenija; sociologija; spolne neenakosti